Effect of Post-Weld Heat Treatment on the Fatigue Behavior of Medium-Strength Carbon Steel Weldments - Byeong-Choon Goo (MDPI AG, 2021)
Railway vehicle makers manufacture the bogie frame by welding medium-strength carbon steel sheets. It has been a long-standing practice to perform post-weld heat treatment (PWHT) to remove welding-residual stress, but rail car manufacturers are moving toward producing bogie frames without PWHT. Since securing the fatigue strength of the bogie frame is essential for vehicle operation safety, it is necessary to systematically evaluate the effects of PWHT on hardness, microstructure, mechanical properties, corrosion, fatigue strength, etc. In this study, small-scale welding specimens and full-size components were produced using S355JR used in general structures, automobiles, shipbuilding, railroad vehicles, etc. The effect of PWHT on material properties-the hardness of the base material, heat-affected zone and weld metal, microstructure, shock absorption energy, yield strength, tensile strength, and fatigue were investigated. When the weld specimen was annealed at 590 °C and 800 °C for 1 h, the yield strength and tensile strength of the specimen decreased, but the elongation increased. For specimens not heat-treated, the parent material’s yield strength, the yield strength in HAZ, and the yield strength of the weld metal were 350 MPa, 345 MPa, and 340 MPa. For specimens heat-treated at 590 °C, they were 350 MPa, 345 MPa, and 340 MPa. For specimens heat-treated at 800 °C, they were 350 MPa, 345 MPa, and 340 MPa. Annealing heat treatment of the specimen at 800 °C homogenized the structure of the weldments similar to that of the base material and slightly improved the shock absorption energy. For specimens not heat-treated, the Charpy impact absorption energies at 20 °C of the parent material and weld metal were 291.5 J and 187 J. For specimens heat-treated at 590 °C, they were 276 J and 166 J. For specimens heat-treated at 800 °C, the Charpy impact absorption energy at 20 °C of the parent material was 299 J. PWHT at 590 °C had the effect of slightly improving the fatigue limit of the specimen but lowered the fatigue limit by 10.8% for the component specimen.